Pengaruh Budaya terhadap Efektivitas Organisasi : Dimensi Budaya Hofstede - Chairuman Armia (Jurnal Akuntansi dan Auditing Indonesia)
This paper uses Hofstede’s (1980) cultural dimension of power distance, uncertainty avoidance, individualism/collectivism, and masculinity/femininity to examine the relative influence of culure on the uses of performance evaluation system in measuring the organizational effectiveness